2016
DOI: 10.1021/acs.jpcc.6b02549
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water on the Electrified Ionic Liquid/Solid Interface: A Direct Observation of the Transition from a Multilayered Structure to a Double-Layer Structure

Abstract: Ionic liquids are potential designer electrolytes for energy storage devices such as batteries and capacitors wherein by changing the cation and anion of the ionic liquid (IL) the solid/liquid interface can be tuned, thereby influencing the charge and mass transfer processes. In this paper, we show the influence of water on the electrified ionic liquid 1-ethyl-3-methyl­imidazolium trifluoro­methyl­sulfonate ([Emim]­TfO)/Au(111) interface using in situ atomic force microscopy (AFM) and spectroscopy. A clear “wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
116
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 56 publications
6
116
0
Order By: Relevance
“…In additionally wetted ionic liquids, layering was also present, but the jumps between the innermost layer and surface were larger, suggesting that water forms an adsorption layer on the mica surface, altering the interface structure [105]. The effect of higher amounts of water on the interface structure was examined by Cui et al [114] using 1-ethyl-3-methylimidazolium trifluoromethylsulfonate ([EMIm][TfO]) in contact with Au (111). They found that the number of layers detected by the force-separation curves decreased with increasing water content.…”
Section: Influence Of Watermentioning
confidence: 99%
See 2 more Smart Citations
“…In additionally wetted ionic liquids, layering was also present, but the jumps between the innermost layer and surface were larger, suggesting that water forms an adsorption layer on the mica surface, altering the interface structure [105]. The effect of higher amounts of water on the interface structure was examined by Cui et al [114] using 1-ethyl-3-methylimidazolium trifluoromethylsulfonate ([EMIm][TfO]) in contact with Au (111). They found that the number of layers detected by the force-separation curves decreased with increasing water content.…”
Section: Influence Of Watermentioning
confidence: 99%
“…This compression is weakened at an intermediate concentration, indicating a mixture of separated molecules and micelles, while at a high concentration, the compression was found to be the highest at 4.4 nN/Å, reflecting the dense micellar layering. The effect of higher amounts of water on the interface structure was examined by Cui et al [114] using 1-ethyl-3-methylimidazolium trifluoromethylsulfonate ([EMIm][TfO]) in contact with Au (111). They found that the number of layers detected by the force-separation curves decreased with increasing water content.…”
Section: Influence Of Watermentioning
confidence: 99%
See 1 more Smart Citation
“…[176][177] A recent paper by Endres et al using in situ atomic force microscopy and vibrational spectroscopy demonstrates that the structure of the innermost (Stern) layer in 1-ethyl-3methylimidazolium trifluoromethylsulfonate + water on Au(111) depend on both the applied potential and quantity of water. 178 Their work reveals a transition from a multilayer structure to a classical double layer structure at -1.0 V vs Pt Quasi-reference electrode (QRE) upon changing the water concentration from 30 to 50 vol. %.…”
Section: Protic Ils Are Formed By Simple Proton Transfer Between Neatmentioning
confidence: 96%
“…%. 178 Water will certainly be active within the electrochemical double layer (EDL), affecting RED/OX processes, altering electrochemical windows, and possibly degrading the electrode surface. 179 Water sorption from the atmosphere has been studied in aprotic imidazolium-based ILs by gravimetric analysis, 164 with near-infrared spectroscopy, 162 by volumetric analysis from a levitated ionic liquid droplet, 174 and in tandem with electrochemistry.…”
Section: Protic Ils Are Formed By Simple Proton Transfer Between Neatmentioning
confidence: 99%